Analisis Kebutuhan Pengembangan Buku Interaktif Berbasis Augmented Reality (AR) untuk Meningkatkan Minat Baca Anak-Anak - Aswan, Dedy (Peneliti.net, 2024)
This study aims to explore children's preferences for books and interactive technologies and to identify the potential of Augmented Reality (AR) in enhancing their reading interest. A quantitative survey was conducted with children to gather data on their preferences for visual and multimedia elements in books. The results show that 85% of children like books with many pictures, and 78% feel that interesting pictures help them better understand the story. Additionally, 92% of children enjoy watching videos on their phones, and 83% are interested in books that include educational videos. Notably, 87% of children expressed a desire to try reading books with AR technology and enjoy AR features such as 3D animations, educational games, and simulations. These findings indicate that AR-based books have great potential to increase children's interest in reading and support their learning in a more enjoyable and effective way. By developing books that are appealing and tailored to children's needs, AR can become an innovative tool that helps cultivate a love for reading and improve children's literacy skills. This study suggests that integrating AR technology into children's books can provide a richer and more interactive reading experience, meeting their visual and interactive preferences and enhancing their engagement and motivation to read.